Sistem Keamanan Pintu Rumah Berdasarkan Pengenalan Wajah Menggunakan Kamera Berbasis Internet of Things - Assyifa Sabitaswari, Dhia; Djatmiko, Wisnu; Bintoro, Jusuf (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2022)
This study aims to design and develop a security system an effort to provide a sense of security by using an Internet of Things- as a detection medium to be able to detect faces that are known or unknown by the system at the door of the house, thus helping homeowners to monitor anyone who wants to enter the house and make it easy to access home. This study uses the Research and Development (RnD) method with the Borg and Gall model which includes; 1) Analysis Stage, 2) Design Stage, 3) Development Stage, and 4) Stage Testing. The results of the study show a home door security system based on facial recognition-based camera internet of things can function properly with a range a successful presentation 45cm and 60cm. This system was successfully developed with an emergency theft system and an indicator in the form of a speaker to make a sound if no one is at home when the homeowner presses the button on Blynk. With the Blynk application, homeowners can receive notifications from the system and can monitor display video streams and control the system remotely.